Crypto Minning : Indonesia Carbon Tax Challenges and Safeguarding International Commitment on Human Security - Ika Riswanti Putranti (Research Collaboration Community (RCC), 2022)
The need for financial transactions in the virtual world that continues to grow demands an increase in the speed, quality, and quantity of various innovations and discoveries in the field of financial technology known as cryptocurrency. This discovery encourages various developments of the virtual world economy which is increasingly diverse and growing according to the needs and interests of existing economic actors. Cryptocurrencies are currently only considered as digital assets that can be traded so they are not recognized as a means of payment. However, cryptocurrency trading in Indonesia is a fast-growing field, so its economic value continues to rise rapidly. This encourages the emergence of crypto mining businesses that tend to use large amounts of electricity. The issue of carbon footprint in cryto mining has in several ways been the cause of the prohibition of this activity. In Indonesia, this activity is still not banned, in 2022 a carbon tax will be applied where every kilogram of carbon equivalent emissions that exceed a certain cap will be subjected to Rp-30 (0.21 cent dollar) tax. So the paper tries to analyze the extent to which this carbon tax will affect crypto mining in Indonesia and how the mitigation of crypto mining's carbon footprint can be managed through proper regulation without disturbing the crypto economic sector that is blooming in Indonesia.